Optimalisasi Ventilasi Ruang Kelas untuk Mencegah Penularan Covid-19 dengan Setting Experiment: Indonesia - Komarudin Komarudin; Alfian Nasution; Yohanes Baptista Indra Kurniadri; Suharjito Suharjito (Fakultas Teknik Universitas Tulang Bawang, 2023)
The spread of the SARS-CoV-2 virus has forced many schools to implement health protocols such as wearing masks, social distancing, and limiting the number of students in classrooms when face-to-face learning resumes as it did before the pandemic. This is due to the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC) stating that Covid-19 can spread through the air (airborne). In addition to implementing health protocols, another important thing is to maintain classroom ventilation. By increasing the ventilation of outside air into the classroom, the risk of virus transmission can be reduced, and the indoor air quality can be improved. Introducing as much outside air as possible into the room is one important way to prevent the spread of Covid-19 because it can reduce the concentration of the virus in the room. ASHRAE (American Society of Heating, Refrigerating, and Air Conditioning Engineers) recommends a minimum of 6 ACH (Air Change per Hour) for classrooms. Research conducted on one middle school classroom in Tangerang Selatan, equipped with 2 AC units and 1 window, showed that the ASHRAE standard can be met by opening the window at least 50% during learning activities and turning on 1 AC unit with the fan setting at full speed to achieve an ACH greater than 6. If besides wanting to prevent the transmission of Covid-19, you also want to create comfort during the learning process, you can turn on both AC units with the fan setting at low to full speed. Keywords: Airborne, ASHRAE, Social distancing, US-CDC, WHO